GHB acid: A rage or reprive - Prakhar Kapoor; Revati Deshmukh; Ipsita Kukreja (Wolters Kluwer Medknow Publications, 2013)
Gamma-hydroxybutyric acid (GHB) is a naturally occurring analog of gamma-aminobutyric acid (GABA) that has been used in research and clinical medicine for many years. GHB was used clinically as an anesthetic in the 1960s but was withdrawn due to side effects that included seizures and coma. GHB has been implicated in a number of crime types; most notably in drug-facilitated sexual assault. GHB is abused by three main groups of users: Body builders who use the substance believing that it stimulated the release of growth hormone; sexual predators who covertly administer the drug for its sedative and amnesic effects and club-goers (rave parties) who take the drug for its euphoric effects. The short-lived hypnotic effects, relative safety and widespread availability of the drug have made it particularly well suited to this role. The drug has an addictive potential if used for long term. The primary effects of GHB use are those of a CNS depressant and therefore range from relaxation, to euphoria, confusion, amnesia, hallucinations, and coma. Despite the increased regulation, GHB remains widely available through the Internet where one can easily purchase the necessary reagents as well as recipes for home production. There are reports of patients being unresponsive to painful stimuli and cases of oral self-mutilations linked to the abuse of GHB, though quiet rare. Such cases should remind odontologists that intra-oral lesions may be the result of self-mutilation either due to mental illness or altered states caused by the use of prescription or non-prescription drugs.